Performance of a hydrokinetic turbine using a theoretical approach - S. Hazim; A. El Ouatouati; M. Taha Janan; A. Ghennioui (Energy Reports, 2020)
Regarding the interest in renewable energies, several sources of energy production have been studied and still under improvement. In this work, we are interested in harnessing marine energy currents exploiting the hydrokinetic turbines. The purpose of this study is to provide a comprehensive assessment of the hydrodynamic loads of a 3-blade horizontal-axis marine turbine using a rotor model adapted to the Moroccan potential. For that, the Blade Element Momentum (BEM) is used to calculate the hydrodynamic loads, to estimate the energetic performance, and to determine the blade optimal parameters for a turbine. In additions, the resulting equations are solved in order to obtain the hydrodynamic loads. For validation, a comparison of pressure coefficients along the chord length was made with the results of the Blade software. The Computations were accomplished for a specific NACA profile.
Keywords: 330; BEM theory; Hydrodynamics performance; Hydrokinetic turbine; Marine current turbine